Gênero e diversidade: as reitoras da ufg - CALDAS, Terezinha Maria Leite (2011)
This study aims to assess the trajectory of the two women who occupied the Presidency of the Federal University of Goiás (UFG) since its founding fifty years ago; focusing on the impediments and/or facilitating factors of the female ascension to the highest University position. Maria do Rosário Cassimiro was the UFG President from 1982 to 1985, and Milca Severino Pereira held the position between 1998 and 2005. This thesis discusses the impediments and facilitating elements of the female career advancement, the gender discrimination at the public arena, the relevancy of people s subjective choices, the legitimacy of male supremacy and served to guide the interpretation of the researched empiric data. The data was acquired through semistructured interviews. And the thesis was written as narrative interview form. The field research pointed to an overvalue of women s paid work, which was recognized by both, being of the highest importance. Therefore, other aspects of their life such as social, emotional and family relations were lived as secondary priority as they made choices renouncing all that could be an obstacle to their professional advancement.